LEVERAGING PROJECT-BASED LEARNING: ENGLISH TEACHERS’ VIEWS ON ENHANCING SPEAKING SKILLS IN VOCATIONAL SETTINGS - Ayy, Ayu Diana Cahya Ningtatia Putri; Afrianto (Indonesian Journal of Educational Development (IJED), 2025)
This research examines the implementation of Project-Based Learning (PBL) to enhance speaking skills in a vocational school in Lampung. The investigation utilises a subjective strategy, centring on English teachers' recognitions and encounters in utilising PBL. The considering points to investigate how English instructors see the viability of PBL in progressing professional students' talking abilities, recognize challenges in actualizing PBL, and report procedures and best hones utilised by instructors. The data were collected through in-depth interviews with English instructors at SMK Tri Sukses. The discoveries uncover that PBL essentially improves understudy inspiration and engagement in learning English. Instructors detailed adjusting ventures to particular professional settings, such as making application letters for bike-building understudies and realistic plan ventures for Mixed media understudies. Challenges included innovation impediments, which were tended to through coordination with school offices. The ponder highlights the significance of contextualising dialect learning to students' zones of skill and the vital part of instructor inspiration in effective PBL execution. Comes about show that PBL progresses not as it were students' talking abilities but moreover their by and large dialect capability and proficient competencies. This inquiry contributes to the understanding of PBL's viability in professional English instruction and gives viable bits of knowledge for teachers executing PBL in comparable settings. The discoveries propose that PBL, when custom fitted to particular professional needs, can make a more locks in and compelling learning environment for creating English talking abilities in professional instruction.